International organizations the politics and processes of global governance - Karns, Margaret P. (Lynne Rienner Pub., 2010)
Professors Karns and Mingst trace the evolving roles of the full range of IGOs, NGOs, state and nonstate actors, norms, rules, and other pieces of global governance. In addition, four issue-based chapters on peace and security, development, human rights, and the environment present current case studies and examine the elements of global and regional governance that are involved. New case studies include the conflict in the DRC, the current global economic crisis, and efforts to combat human trafficking and other slave-like practices. Throughout, the authors highlight questions of the legitimacy, accountability, and effectiveness of global governance.